The Relevance of Sayyid Jamaluddin al Afghani's Thoughts for Indonesia in Facing the Challenges of Globalisation - Risa Bhinekawati; Ita Sitasari; Muhammad Najib (International Economic and Finance Review, 2022)
This article discusses the life journey of Sayyid Jamaluddin Al Afghani (1938-1897), his thoughts and teachings on Islamic modernisation and their relevance for Indonesia in facing today’s free trade. Using the historical narrative writing method, this article describes the history of Afghani’s life and works. Furthermore, the author analyses the main points of Afghani’s thoughts, especially in terms of rationalism, the six principles of truth (Arkan al-Sittah) in dealing with materialism, Qadha and Qadar, and the role of government, and writes down their relevance for Indonesia in facing competition in the era of globalisation. In the face of global competition, the author argues that Afghani’s thinking can be applied to Indonesia at two levels. At the country level, Indonesia can use it to improve its economic diplomacy strategy. Meanwhile, at the community level, the Indonesian people can apply it in determining the choice of social and economic activities to be more in favour of domestic products. With the collective strength of the community, it is hoped that Indonesia can be economically independent. Keywords: al-Radd ‘ala al-Dahriyyin, Arkan al-Sittah, Globalisation, Jamaluddin al-Afghani, Qadha and Qadar